Myocardial dysfunction and cardiovascular disease in type 2 diabetes. (18th May 2016) - Ofstad, Anne Pernille
Abstract: Type 2 diabetes mellitus (T2DM) is strongly associated with increased risk of myocardial dysfunction and cardiovascular disease (CVD), two separate conditions which often co-exist and influence each other's course. The prevalence of myocardial dysfunction may be as high as 75% in T2DM populations but is often overlooked due to the initial asymptomatic nature of the disease, complicating co-morbidities such as coronary artery disease (CAD) and obesity, and the lack of consensus on diagnostic criteria. More sensitive echocardiographic applications are furthermore needed to improve detection of early subclinical changes in myocardial function which do not affect conventional echocardiographic parameters. The pathophysiology of the diabetic myocardial dysfunction is not fully elucidated, but involves hyperglycemia and high levels of free fatty acids. It evolves over several years and increases the risk of developing overt HF, and is suggested to at least in part account for the worse outcome seen in T2DM individuals after cardiac events. CAD and stroke are the most frequent CV manifestations among T2DM patients and relate to a large degree to the accelerated atherosclerosis driven by inflammation. Diagnosing CAD is challenging due to the lower sensitivity inherent in the diagnostic tests and there is thus a need for new biomarkers to improve prediction and detection of CAD. It seems that a multi-factorial approach (i.e. targeting several CV risk factors simultaneously) is superior to a strict glucose lowering strategy in reducing risk for macrovascular events, and recent research may even support an effect also on HF outcomes.